Pengaruh Penduduk Miskin Dan Pengangguran Terhadap Pertumbuhan Ekonomi Wilayah Mataraman Provinsi Jawa Timur Tahun 2017-2020 - Renna Dewi Zahari (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The purpose of this research is to see how the poor and unemployed affect economic growth in the Mataraman area of East Java Province from 2017 to 2020. The data used is panel data from the Mataraman area of East Java Province, which spans the years 2017 to 2020. The impoverished and unemployment are independent variables, while economic growth is the dependent variable. Multiple linear regression with the Fixed Effects Model was employed as an analytical technique (FEM). The poor population's partial regression results have little effect on economic growth, whereas unemployment has a negative and considerable impact on growth. The economic growth of 16 cities/regencies in the Mataraman area of East Java is influenced by both the poor and the unemployed at the same time, with a coefficient of determination of 67 percent in this study.